Are Sovereign Debt Secondary Market Returns Sensitive to Macroecoriomic Fundamentals? : Evidence from the Contemporary and Interwar Markets. (IMF Working Papers; Working Paper ;, 1990)
The insensitivity of sovereign loan secondary market returns to macroeconomic fundamentals has been attributed to market illiquidity and the absence of publicly reported transactional prices. During the 1920s and 1930s sovereign bonds were traded in an active market and weekly transactional prices were publicly available. This paper shows that price changes from both eras are insensitive to unexpected changes in key external and country-specific macroeconomic aggregates, but that returns are moved by individual agent announcements that presage changes in future lending. The results, which contrast with studies of U.S. equities, indicate that the sovereignty of the issuer matters more than the type of debt contract.